Rereading Huizinga : autumn of the middle ages, a century later - Arnade, Peter J.; Howell, Martha C.; Lem, Anton van der (Amsterdam University Press, 2019)
This edited volume is a reappraisal of the legacy and historiographical impact of Johan Huizinga's 1919 masterwork for the centenary of its publication in the field of medieval history, art history, and cultural studies.
Keywords: Huizinga, Johan, -- 1872-1945. -- Herfsttij der Middeleeuwen.; Herfsttij der Middeleeuwen (Huizinga, Johan); France -- Civilization -- 1328-1600.; Netherlands -- Civilization.; Civilization, Medieval.; France -- Civilisation -- 1328-1600.; Pays-Bas -- Civilisation.; Civilisation médiévale.; European history.; Medieval history.; HISTORY -- Europe -- Western.; Civilization; Civilization, Medieval; France; Netherlands; 1328-1600; Art and Culture.; Burgundian Court.; Burgundian Netherlands.; Medieval History.; Electronic books.